Preemptive Analgesia With Bupivacaine for Segmental Mastectomy. Issue 3 (1st May 2006) - Vallejo, Manuel C.; Phelps, Amy L.; Sah, Neera; Romeo, Ryan C.; Falk, Jeffrey S.; Johnson, Ronald R.; Keenan, Donald M.; Bonaventura, Margueritte A.; Edington, Howard D.
Abstract : Background and Objectives: Preemptive analgesia is the concept of providing analgesia before surgical incision, resulting in less postoperative pain. The purpose of this study is to determine if preemptive and/or postoperative local anesthetic infiltration of bupivacaine in patients undergoing segmental mastectomy results in less postoperative pain compared with patients receiving placebo. Methods: In this prospective, double-blinded study, 120 patients were randomized into 4 groups: group 1, preincisional (10 mL) and postoperative (10 mL) wound infiltration of 0.5% bupivicaine, (+Pre+Post); group 2, preincisional bupivacaine (10 mL) and postoperative infiltration (10 mL) of placebo (normal saline solution), (+Pre−Post); group 3, preincisional placebo (10 mL) and postoperative bupivacaine (10 mL), (−Pre+Post); or group 4, preincisional (10 mL) and postoperative infiltration of placebo (10 mL), (−Pre−Post). All patients received a standardized laryngeal mask general anesthetic. Data were recorded at the following time intervals: preoperative admission, postanesthesia care unit (PACU) admission, PACU stay, stepdown-unit admission, stepdown-unit stay, hospital discharge, and 24 hours post operation. Results: No difference was noted with respect to preoperative pain visual analog scale (VAS, 0-100 mm), surgical duration, PACU stay time, stepdown-unit stay time, incidence of postoperative nausea, or treatment for nausea in all measured time periods. The placebo group (group 4) had significantly higher mean pain VAS scores during the early postoperative period (PACU admission and PACU stay) compared to the other groups (PACU admission: group 1 = 2 ± 8, group 2 = 4 ± 11, group 3 = 3 ± 15, group 4 = 17 ± 21, P < .01; PACU stay: group 1 = 6 ± 13, group 2 = 6 ± 10, group 3 = 10 ± 21, group 4 = 20 ± 18, P < .01). Likewise, the number of patients who reported pain (pain frequency) was significantly higher in group 4 (placebo) compared with all other groups at PACU admission, PACU stay, stepdown-unit admission, and stepdown-unit stay ( P ≤ .01). Conclusion: Preincisional and/or postoperative wound bupivacaine infiltration lacks preemptive analgesic effects for segmental mastectomy.